Marine sediment nitrogen isotopes and their implications for the nitrogen cycle in the sulfate-methane transition zone - Yang, Xin; Zhang, Yihao; Sun, Xiaoming; Xu, Li; Chen, TingTing (Frontiers in Marine Science, 2023)
Introduction Recent work has proposed that the nitrogen isotopes in marine sediments can be impacted by anaerobic oxidation of methane (AOM), since nitrogen uptake by anaerobic methanotrophic archaea (ANME) modifies the nitrogen isotope compositions of bulk sediment. Thus, unraveling the AOM-driven nitrogen cycle in the sulfate-methane transition zone (SMTZ) becomes significant. Additional study of the nitrogen cycle between sediment and interstitial water in SMTZ is needed. Methods To better understand the nitrogen cycle in the SMTZ, we analyzed NH4+ concentrations of interstitial water and nitrogen isotopes of sediment in the core GC10 from the southwestern Taiwan Basin in the South China Sea. Results The defined SMTZ is located at 560–830 cmbsf, based on methane and sulfate concentrations, as well as TS/TOC ratios, δ13CTIC and δ34S values. In the SMTZ, the NH4+ concentration decreases, the δ15NTN shows a negative excursion, δ15Ndecarb displays a positive excursion. Discussions NH4+ concentration decrease is interpreted by sulfate-reducing ammonium oxidation (SRAO). The δ15NTN shows negative excursion, which is most likely interpreted to N2 (δ15N=0‰) released from SRAO that was fixed into marine sediment via ANME nitrogen fixation. The δ15Ndecarb shows a negative correlation with NH4+ concentrations, indicating that it was controlled by organic matter decomposition. In the SMTZ, the methane competes with organic matter for becoming the substrate of sulfate reduction bacteria, which possibly decreases the organic matter degradation rate and causes δ15Ndecarb relative positive excursion. Although δ15Ndecarb is controlled by organic matter degradation, δ15NTN still reveals a negative excursion in the SMTZ. This likely indicates that nitrogen uptake by ANME/AOM microbial consortiums mainly modifies the nitrogen isotope of soluble nitrogen in the SMTZ. Conclusions This study indicates unique geochemistry processes in SMTZ will modify nitrogen characteristics in sediment/interstitial water, and the latter can serve as a proxy for AOM.